Towards a better understanding of informal financial service interventions in West Africa: Investigating impact, evolution, and key challenges. - Sawyer, Melita Antoinette (Tufts University. Tisch Library., 2019)
This dissertation adds to our knowledge on the role of simple informal savings devices in helping households in West Africa cope with shocks, smooth consumption, and invest in the short term and the longer term. The studies presented herein find that a simple savings device can help households smooth consumption in the face of serious health shocks. In Niger, households with a simple lockbox who faced a health shock were less likely to go a day without food. The households' self-insurance strategies improve as they are more likely to use cash savings than selling assets or using loans. I also find that savings group usage in Benin can endure for years after NGO support ends. The groups continue to provide members with financial services that the members use and can benefit from. On average, members' savings amounts increase over time, and "share-out" amounts increase over time facilitating investment in productive assets for some members. I also find that low levels of literacy are a challenge to optimal usage of informal financial tools including SMS messages and ASCAs. However, the recent research shows that adults can learn to read and suggests that adult literacy programs may be improved with more practice, explicit instruction in each stage of literacy acquisition, and increased flexibility.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Fletcher School of Law and Diplomacy.; Advisor: Jenny Aker.; Committee: Kimberley Wilson, and Julie Schaffner.; Keywords: Economics, and Adult education.